Cardiac amyloidosis: a case report - Viñas-Mendieta, Adriana E. (2022)
Amyloidosis is a multisystem disease caused by infiltration of misfolded proteins; cardiac involvement determines its prognosis. There are several types of precursor proteins capable of causing the disease; however, only two affect the heart, clonal immunoglobulin light chains (AL) and tetrameric transthyretin (TTR) protein. It is an underdiagnosed disease and, in late stages, it has a poor prognosis. We present the case of an older adult patient with progressive cardiac and extracardiac manifestations, as well as laboratory and echocardiographic criteria that brought us closer to the diagnosis of cardiac amyloidosis and also allowed us to assess the prognosis. The patient had a torpid evolution with a fatal outcome. The pathological anatomy studies allowed us to confirm our diagnostic presumption.